2004
DOI: 10.1111/j.1348-0421.2004.tb03546.x
|View full text |Cite
|
Sign up to set email alerts
|

Antibody Reactive to a Hepatitis C Virus (HCV)‐Derived Peptide Capable of Inducing HLA‐A2 Restricted Cytotoxic T Lymphocytes Is Detectable in a Majority of HCV‐Infected Individuals without HLA‐A2 Restriction

Abstract: Hepatitis C virus (HCV) is a single‐strand RNA virus. Approximately 170 million people around the world are persistently infected and are at risk of liver cirrhosis or cancer. There is an urgent need to develop both therapeutic and diagnostic modalities of HCV. One approach to achieve these goals would be to determine highly immunodominant HCV peptides which are recognized by both cellular and humoral immunities. This study reports one such peptide, HCV‐core protein at positions 35–44, having HLA‐A2 binding mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2005
2005
2009
2009

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 25 publications
1
15
0
Order By: Relevance
“…Since HCV is a highly heterogeneous virus and, in some circumstances, even a single amino acid variation within CTL epitopes facilitates viral escape from host immunity (1,8), amino acid mutation in these individuals may be the most plausible explanation. We previously reported that the HCV1b 35-44 peptide induced specific CTLs from the PBMCs of HCV1b-infected patients (26). In this study, the HCV2a 35-44 peptide, which has the same amino acid sequence as HCV1b 35-44, was also found to be immunogenic in some patients, but the rate of successful CTL induction was less than 50%.…”
Section: Cd8mentioning
confidence: 68%
“…Since HCV is a highly heterogeneous virus and, in some circumstances, even a single amino acid variation within CTL epitopes facilitates viral escape from host immunity (1,8), amino acid mutation in these individuals may be the most plausible explanation. We previously reported that the HCV1b 35-44 peptide induced specific CTLs from the PBMCs of HCV1b-infected patients (26). In this study, the HCV2a 35-44 peptide, which has the same amino acid sequence as HCV1b 35-44, was also found to be immunogenic in some patients, but the rate of successful CTL induction was less than 50%.…”
Section: Cd8mentioning
confidence: 68%
“…The cross-reactivity of anti-C35 IgG was observed in the sera of HTLV-1 + patients, which could in part be due to the fact that the HTLV-1 envelope protein also possesses the same previously reported Wne epitomic sequence (LPRR) as the C35 peptide at positions 37-40 [17]. The HIV tat protein also shares Wve amino acids (PRRGP) with the C35 peptide at positions 38-42; furthermore, the HIV envelope protein shares Wve amino acids (RRGPR) with the C35 peptide at positions 39-43.…”
Section: Discussionmentioning
confidence: 89%
“…We recently found two unique Abs speciWc to HCV1b-derived peptides; one of these Abs was speciWc to the human leukocyte antigen (HLA)-A2-restricted CTL epitope peptide of the HCV1b core protein at positions 35-44 (anti-C35 Ab), and the other Ab was speciWc to the HLA-A24-restricted CTL epitope peptide of the NS5A protein at positions 2132-2140 (anti-NS5A2132 Ab) [17]. These two Abs were detected in a majority of a sample of patients with HCV + , regardless of diVerences in terms of their disease conditions, but the biological activities of these Abs remain unclear at the present time.…”
Section: Introductionmentioning
confidence: 99%
“…These initial results were consistent with a protective effect against tumor growth of T cell-mediated immune response directed to HCC-associated antigens. This hypothesis has been subsequently corroborated by the identification of antigen-specific T cells (at tumor site and in periphery) in HCC patients, with specificity for different classes of tumor-associated antigens including cancer testis [9,10], self antigens as AFP and SART-1 [11,12], as well as viral epitopes [13,14].…”
Section: See Articles Pages 246-253 and 254-262mentioning
confidence: 95%
“…These initial results were consistent with a protective effect against tumor growth of T cell-mediated immune response directed to HCC-associated antigens. This hypothesis has been subsequently corroborated by the identification of antigen-specific T cells (at tumor site and in periphery) in HCC patients, with specificity for different classes of tumor-associated antigens including cancer testis [9,10], self antigens as AFP and SART-1 [11,12], as well as viral epitopes [13,14].Two papers in this issue of the Journal [15,16] provide further evidence for the contrasting roles of the immune system in HCC. In the first study Unitt and co-workers show that lymphocyte infiltration of the tumor and a high CD4 + :CD8 + T cell ratio are associated with a reduced risk of tumor recurrence following liver transplantation.…”
mentioning
confidence: 96%